Macroeconomic determinants of Household Consumption in selected West African countries - Chimere Okechukwu Iheonu; Tochukwu Nwachukwu (African Governance and Development Institute (AGDI), 2020)
This study investigates the macroeconomic determinants of household consumption in selected West African countries. The study employed the panel augmented mean group procedure which accounts for heterogeneity and cross sectional dependence in the modelling exercise for the period 1989 to 2018. Empirical results reveal that "gross domestic product per capita" and "domestic credit to the private sector" significantly improve household consumption in the selected West African countries as a whole. However, country-specific results show differences in terms of the magnitude of the coefficients, the significance and even the signs of the regressors. Policy recommendations based on these findings are discussed.
Keywords: E21; O10; 330; Household consumption; West Africa